Cultural and morphological variability among different isolates of Sclerotinia sclerotiorum - Dubey, Prajanya; Singh, Sushil Kumar; Mishra, Rishabhdev; Rahul, S N (Indian Journal of Plant Protection, 2025)
Pea (Pisum sativum L.), a vital legume globally and in India, is susceptible to various diseases. Among them, stem rot or white mold, caused by Sclerotinia sclerotiorum, is a major threat, impacting numerous plant species. This study focused on this pathogen, isolating it from infected pea plant parts and sclerotia. Pathogenicity of the fungus and virulence of different isolates of S. sclerotiorum was proved by following Koch’s postulates. Symptoms emerged within five days of inoculation, starting as water-soaked lesions and progressing to white, fluffy fungal growth followed by sclerotia formation. In in-vitro, the fungus exhibited rapid growth with most isolates covering petri plates within 96 hours. Sclerotia development varied among isolates, with Lucknow isolate showing the highest number and largest size, while Jaunpur isolate produced the fewest and smallest sclerotia